Land management (specifically controlled heather burning) as a factor controlling carbon loss from upland peat soils - Clutterbuck, Ben (Cranfield University, 2009)
Peatlands contain a significant proportion of the worlds’ total soil carbon, and are commonly assumed to serve as carbon sinks. There is however increasing evidence of carbon loss from peat soils, and DOC concentrations in UK rivers have increased markedly over the past three decades. Numerous drivers for increasing DOC release have been proposed but to date the potential role of land management has not been fully explored. This study examines the potential effects of land management on DOC production and release from upland peat for a series of catchments in the South Pennines and North Yorkshire Moors. Spatial variability in drainage DOC concentration was examined in 50 small headwater catchments (<3 km 2 ) and nine reservoir catchments (1.5-21 km 2 ). A subset of the reservoir catchments was further examined through time to establish any relationship between land management and DOC. Of the factors assessed, representing all combinations of soil type and land use, the proportion of new vegetation burn on blanket peat was consistently identified as the most significant predictor of spatial variation in DOC concentration. Significant relationships were identified between both temperature and sulphate deposition and longer-term DOC concentrations, but no interaction or cumulative effect of these two factors was shown. In contrast, the area of new burn on blanket peat explains more than twice the degree of variance in DOC over the same period. For catchments where no change in the area of new burn was determined, drainage DOC increases were minimal. This study demonstrates that land management activities are important landscape-scale drivers of DOC concentration. Exposed peat surface following burning may be altering peat hydrology and improving conditions for microbial activity and enhanced DOC production. Land management therefore has significant consequence for water utilities facing increased costs of treatment and also for the conservation of blanket bog and blanket peat ecosystems currently managed by fire.